Trend Analysis of Snow Cover Changes Using Statistical Downscaling Model and Climate Scenarios in Sefid-Rud Basin (Iran) - Entezami, Hersh; Mojarrad, Firouz; Darand, Mohammad; Ghaderpour, Ebrahim (Italian journal of engineering geology and environment, 2025)
Investigating the status of snow cover and possible changes due to climate change is a vital and important issue. In the present study, snow cover change trends, possible effect of climatic parameters on these changes and future forecasts of snow cover of Sefid-Rud Basin are investigated using 8-day MOD10A2 products of moderate resolution imaging spectroradiometer (MODIS) sensor for the period 2000-2019. After preparing the snow cover map of all the images of the study period, the percentage of snow cover is determined. In each of the 11 subbasins, one pixel is selected to demonstrate the results in more detail. Then based on the climate parameters of the CanESM2 climate model from the fifth climate change report (FCCR) and utilizing the statistical downscaling model (SDSM), climate parameters effective in changes of snow cover of the 11 pixels for the period of 2000-2005 are determined. To validate the effect of these results on snow cover change patterns, the results of the 2006-2019 period are compared with the snow cover obtained from satellite images. Finally, by determining the relationship between climatic parameters and snow cover and according to the scenarios of FCCR, the snow cover of the 11 pixels is calculated for the period 2020-2100. The study of the effect of CanESM2 climatic parameters on snow cover shows that at all 11 pixels, several climatic parameters, particularly temperature and wind speed, impacted the snow cover change patterns. Therefore, to predict future snow cover, climatic data are used based on the scenarios, indicating that snow cover would decrease sharply based on the two scenarios RCP4.5 and RCP8.5, particularly RCP8.5. The results of the model validation and comparison with satellite data show that the accuracy of the SDSM in predicting snow cover is acceptable.